Human-building interaction at work: Findings from an interdisciplinary cross-country survey in Italy. (15th March 2018) - D'Oca, Simona; Pisello, Anna Laura; De Simone, Marilena; Barthelmes, Verena M.; Hong, Tianzhen; Corgnati, Stefano P.
Abstract: This study presents results from an interdisciplinary survey assessing contextual and behavioral factors driving occupants' interaction with building and systems in offices located across three different Mediterranean climates in Turin (Northern), Perugia (Central), and Rende (Southern) Italy. The survey instrument is grounded in an interdisciplinary framework that bridges the gap between building physics and social science environments on the energy- and comfort-related human-building interaction in the workspace. Outcomes of the survey questionnaire provide insights into four key learning objectives: (1) individual occupant's motivational drivers regarding interaction with shared building environmental controls (such as adjustable thermostats, operable windows, blinds and shades, and artificial lighting), (2) group dynamics such as perceived social norms, attitudes, and intention to share controls, (3) occupant perception of the ease of use and knowledge of how to operate control systems, and (4) occupant-perceived comfort, satisfaction, and productivity. This study attempts to identify climatic, cultural, and socio-demographic influencing factors, as well as to establish the validity of the survey instrument and robustness of outcomes for future studies. Also, the paper aims at illustrating why and how social science insights can bring innovative knowledge into the adoption of building technologies in shared contexts, thus enhancing perceived environmental satisfaction and effectiveness of personal indoor climate control in office settings and impacting office workers' productivity and reduced operational energy costs. Highlights: A questionnaire survey assesses contextual and behavioral factors driving human-building interaction in office spaces. The survey uses an interdisciplinary framework integrating building physics and social psychology. The survey has 1160 valid responds from office occupants in three climates of Italy. A general dissatisfaction emerged over the shared control of thermostat settings in office spaces. The survey provides insights into motivational drivers, group dynamics, ease of use and knowledge of control systems.